Konflik Batin dan Mekanisme Pertahanan Diri Tokoh Ikrimah bin Abu Jahal dalam Drama Zaujatān Ṣāliḥatān Karya Ali Ahmad Bakatsir melalui Psikoanalisis Freud - Ramadhani, Yus; Syah, Ahfa Rahman; Novita, Lidya; Amelia, Rosita (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study analyzes the internal conflicts and defense mechanisms of Ikrimah ibn Abu Jahal through the lens of Sigmund Freud’s psychoanalytic framework. Employing a qualitative descriptive-analytical approach that utilizes content analysis and the "showing" method, this library research examines seven dialogue sequences across three scenes, following a four-stage process: data identification, classification of internal conflicts and defense mechanisms, theoretical interpretation, and conclusion. Data collection techniques use documentation techniques which are carried out by collecting, recording and reviewing written sources that are relevant to the research topic. The findings reveal that Ikrimah’s internal conflict is multilayered and progressive, manifesting in three distinct phases: (1) the conflict between upholding and surrendering honor in Scene One; (2) the conflict between recognizing and accepting the truth of Muhammad’s prophethood in Scene Two; and (3) the conflict between the burden of his former identity and the emergence of a new identity in Scene Four. To navigate these dilemmas, Ikrimah employs several defense mechanisms: (1) displacement, in which psychic conflict is redirected into physical flight; (2) rationalization, wherein he constructs justifications to conceal his perceived inadequacy and shame; (3) denial, through which he rejects the reality of Muhammad’s prophethood; and (4) repression, the most foundational mechanism, evidenced by his suppression of his underlying belief in the truth of the prophethood.